Higher Education Reforms in Romania: Between the Bologna Process and National Challenges - Curaj, Adrian; Deca, Ligia; Egron-Polak, Eva; Salmi, Jamil (Springer Nature, 2015)
Higher Education; Educational Policy and Politics; International and Comparative Education; International higher education arena; Higher education reforms; UEFISCDI; Evidence-based policy making; Higher education in Romania; Higher education public policies